Mediasi Budaya dalam Pengasuhan Digital: Integrasi Nilai-Nilai Islam dan Kearifan Lokal Madura Untuk Membangun Resiliensi Anak Usia Dini - Yayik Indah Susnita; Khamim Zarkasih Putro (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The shift from conventional to digital parenting presents concrete challenges for Madurese Muslim families who must balance technological literacy with the preservation of cultural values. The technology literacy gap between parents and children leads to the declining transmission of bhapa’ bhabhu’ ghuru rato (respect for father, mother, teacher, and leader), ta’dzim (courtesy), and andhap asor (humility) in daily family life. Existing digital parenting scholarship has been largely shaped by Western-secular perspectives that overlook how conservative religious communities negotiate technology use through religious and local cultural frameworks. This study explores how Islamic values and Madurese local wisdom shape digital parenting practices and their implications for early childhood digital resilience. A six-month qualitative case study was conducted at PAUD Al-Hikmah Pamekasan using non-participatory observation and semi-structured interviews with ten key informants. Reflexive thematic analysis following Braun and Clarke’s six iterative stages was applied to identify patterns and themes. Three cultural mediation patterns were identified: technology filtering based on dual religious and cultural criteria, prioritization of physical interaction through traditional games, and family-school partnerships navigating implementation tensions. Children develop dual competencies by appreciating traditional values while engaging with digital media selectively. This study recommends that digital parenting programs integrate religious perspectives and actively involve local religious leaders as strategic implementation partners.